Usability of American Sign Language Videos for Presenting Mathematics Assessment Content. (12th April 2018) - Hansen, Eric G; Loew, Ruth C; Laitusis, Cara C; Kushalnagar, Poorna; Pagliaro, Claudia M; Kurz, Christopher
Abstract: There is considerable interest in determining whether high-quality American Sign Language videos can be used as an accommodation in tests of mathematics at both K-12 and postsecondary levels; and in learning more about the usability (e.g., comprehensibility) of ASL videos with two different types of signers – avatar (animated figure) and human. The researchers describe the results of administering each of nine pre-college mathematics items in both avatar and human versions to each of 31 Deaf participants with high school and post-high school backgrounds. This study differed from earlier studies by obliging the participants to rely on the ASL videos to answer the items. While participants preferred the human version over the avatar version (apparently due largely to the better expressiveness and fluency of the human), there was no discernible relationship between mathematics performance and signed version.